Rhizobium trifolii 0403 Is Capable of Growth in the Absence of Combined Nitrogen - Urban, James E. (1986)
Rhizobium trifolii 0403 was treated with 16.6 mM succinate and other nutrients and thereby induced to grow in nitrogen-free medium. The organism grew microaerophilically on either semisolid or liquid medium, fixing atmospheric nitrogen to meet metabolic needs. Nitrogen fixation was measured via (15)N incorporation (18% (15)N enrichment in 1.5 doublings) and acetylene reduction. Nitrogen-fixing cells had a K(m) for acetylene of 0.07 atm (ca. 7.09 kPa), required about 3% oxygen for optimum growth in liquid medium, and showed a maximal specific activity of 5 nmol of acetylene reduced per min per mg of protein at 0.04 atm (ca. 4.05 kPa) of acetylene. The doubling time on N-free liquid medium ranged from 1 to 5 days, depending on oxygen tension, with an optimum temperature for growth of about 30°C. Nodulation of white clover by the cultures showing in vitro nitrogenase activity indicates that at least part of the population maintained identity with wild-type strain 0403.